Hubungan antara Akses Informasi dengan Pemberian ASI Eksklusif: Hubungan antara Akses Informasi dengan Pemberian ASI Eksklusif - Misdayanti Misdayanti; Sri Damayanty (Afiasi : Jurnal Kesehatan Masyarakat, 2024)
Exclusive breastfeeding for 6 months is stated to be able to reduce under-5 mortality by 13%. After that the child must be given solid food as a supplementary food besides breast milk until the child is 2 years old. Therefore, good nutrition is needed during the growth and development of the brain so that it can develop optimally. In general, women in Indonesia, especially young mothers, are currently aggressively promoting exclusive breastfeeding. However, the exclusive breastfeeding program is still not running optimally as expected. The aim of this studied is to analyzed the correlation between accessibility of information and the success of exclusive breastfeeding. The type of research used is quantitative research with a case control approach. This research was conducted in the Work Area of ​​the Lameuru Health Center. The sample size for each case and control group was 41 mothers of infants aged 6-12 months. Data analysis used the Chi-Square test. The results showed that there was a relationship between access to information and the success of exclusive breastfeeding with a value of p=0.005 (p˂0.05) and odds ratio values ​​of 0.778 and 4.200. This shows that the better/more information about breastfeeding is given to pregnant/breastfeeding women, the higher the success of exclusive breastfeeding. The suggestion from this research is to make innovations to convey information about exclusive breastfeeding, such as making media that is more varied about exclusive breastfeeding, it is hoped that the achievement of exclusive breastfeeding can reach the national target.